Neonatal meningitis at Dr. Pirngadi General Hospital Medan (1972 -1980) - Rahayu Saat; Sondang Tambunan; Adi Sutjipto; Noersida Raid; Bistok Saing (Indonesian Pediatric Society, 1984)
A retrospective study was done on 25 cases of Neonatal Meningitis from 1972 up to 1980 at Dr. Pimgadi Hospital Medan. Their age variation was from one day to one month. The early prominent symptoms were refusal of feeding in 23 cases (92%), decrease of consciousness in 21 cases (84%), fever in 16 cases (64%, convulsion in 15 cases (60%) and vomiting/diarhea in 8 cases (32%). Diagnosis was based on clinical symptoms and Cerebrospinal fluid examination.